Anasakti, the Hindu Ideal, and its Relationship to Well-Being and Orientations to Happiness - Banth, Sudha (Journal of religion and health, 2012)
Anasakti, a Sanskrit term for traits like non-attachment, equipoise, selfless duty orientation, and effort in the absence of concern for the outcome, can be regarded as a Hindu-ideal cluster of personality traits. The relationship of Anasakti with well-being and the three distinct happiness orientations was explored through a study of 676 college students and a sample of 65 yogic practitioners in India. The findings revealed that the yogic practitioners were markedly higher in Anasakti than the secular population. For the yogic population, there was a large correlation between Anasakti and the Orientation to Meaningful Life, and it accounted for more than 20% of the variance in the regression of Anasakti against all the measures of well-being. The yogic population's scores also correlated with several other measures of well-being. The scores of the secular population were less strongly related to the well-being scores; though, several correlation coefficients were statistically significant.